Generation of novelties in the genus Ocimum as a result of natural hybridization: a morphological, genetical and chemical appraisal - Gurav, Tanuja P.; Jayaramaiah, Ramesha H.; Punekar, Sachin A.; Dholakia, Bhushan B.; Giri, Ashok P. (Industrial Crops and Products, 2020)
The genus Ocimum is a boutique of a diverse set of specialized metabolites such as terpenoids and phenylpropanoids. Each Ocimum species and its cultivars represent a characteristic chemical profile. The present study explored the two interspecific Ocimum hybrids originating through a serendipitous natural cross between O. kilimandscharicum and O. basilicum. These two novel Ocimum hybrids exhibited intermediate morphological features of two parental species. Inter simple sequence repeats (ISSR) analysis and DNA barcoding with the plastid non-coding trnH-psbA intergenic spacer region reaffirmed unambiguous parental identification and differentiation of these natural hybrids from other available Ocimum species. Consequently, gas chromatographymass spectrometry-based metabolite profiling of two hybrids identified them as specific chemotypes with the presence of a unique blend of specialized metabolites from the parental species, which are either rich in terpenes or phenylpropanoids. Additionally, expression analysis of key genes from terpenoid and phenylpropanoid pathways corroborated with differential metabolite accumulation. Thus, these two Ocimum hybrids represented the novel chemotypes, which could be useful in commercial cultivation to produce novel essential oil and bioactive constituents. Further, the resulting metabolite diversity could have potential industrial applications in the areas of healthcare, bioremediation, and crop protection.
Keywords: Chemotype; DNA barcoding; Inter Simple Sequence Repeats; Interspecific hybrid; O. basilicum; O. kilimandscharicum; Ocimum